MNCs in Central and Eastern Europe: A Challenge for Development and Sustainable Growth. The Bulgarian Case - Ivona Yackimova; Tamara Todorova (Proceedings of the Fourth International Conference “Globalization and Cultural Differences”, May 19-21, 2000, 2000)
After nearly a decade of profound economic changes and a market transformation, the countries in Central and Eastern Europe now face the challenge of development and sustainable growth. The development priorities include achieving a high income growth for their economies by raising investment rates, strengthening technological capacities and skills, improving the competitiveness of their exports, creating more employment opportunities. An important factor for reaching these goals is the world economic environment and the main economic participants in it as for most of the transition countries (the smaller ones, in particular) the exogenous impetus turns to be the main determinants for the success of the reforms. The reason behind it is the full exhaustion of the national resources (natural, human, capital, financial) in the old "socialist" model and the great economic gap which has existed between the region and the rest of the economic world. The purpose of this paper is to analyze the importance of MNCs activities in Central and Eastern Europe for Marketization of the region and for its effective integration in the globalizing world economy. The authors argue the necessity for more effective actions and policies implementation from government's side to attract strategic investors. The last section deals with the results of an empirical study of MNCs transaction costs activities in Bulgaria and the critical issues relating to the establishment of a better investment climate in the country.
Keywords: F23; F21; 330; Multinational corporations; FDI